Assessment of the linguistic development of Friulian-Italian bilingual children - MAURO, FEDERICA; BURELLI, ALESSANDRA (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2002)
The aim of the present study was to assess the linguistic development of Friulian-Italian bilingual children by means of tests which analyse both the comprehension and production abilities in each language. The study concerns 8 subjects attending the first year of Primary School in Friuli Venezia Giulia, an Italian region where Friulian is considered a minority language and Italian the official and majority language. The main purpose of the investigation was to find out the dominant language of each child and the level (phonology, syntax, lexicon) at which the largest number of cross-linguistic influences occur. The tests were selected from a battery for the assessment of language disorders in children with Italian as first language. The data collected show that only one of the examined subjects can be considered Friulian-dominant. For some subjects the dominance of Friulian was only evident at the comprehension level and, in general, the majority of the children can be considered balanced bilinguals, characterized by a tendency towards mixing and switching. Moreover, the data collected point out that the degree of competence in each language, if compared with the normative values for monolingual subjects, turns out to be on the average. We noticed that the influence of Italian on Friulian is very strong at the lexical level. On the other hand, Friulian does not show traces of the influence of Italian at the syntactic level and sometimes Friulian influences Italian at the syntactic level. As it is common for a minority language to be influenced at the lexical level by the majority and more prestigious language, on the basis of the data collected we can assume that the Italianisation of the Friulian lexicon is a widespread phenomenon concerning the language spoken by the whole linguistic community and not only the language of children and young people.